MEKANISME IMPEACHMENT MENURUT HUKUM TATA NEGARA DAN FIQH SIYASAH - Majid, Abdul (Al-Mazaahib: Jurnal Perbandingan Hukum, 2012)
Presidential impeachment in government institutions are prepared to remind the President, in which tenure may be dismissed at any time in the middle of the road when actually violated the provisions of the Constitution 1945 outlined. Violations committed by the President and / or Vice President, as in Article 7A of the 1945 Constitution after amandmen, this requires a clear legal processes and institutions involved in the impeachment should dare to lay off, if there is strong evidence. Impeachment of the President according to constitutional law and jurisprudence Siyasah essentially the same explanations are only slightly different, Impeachment is a call or prosecution to demand accountability in the form of assembly, and the assembly is known as the Islamic syura (consultation). While the difference is in the Fiqh Siyasah not regulated in detail how the mechanism of impeachment of the President, while the constitutional law set out in the Constitution 1945 and the Law on the Constitutional Court No.. 24 of 2003. In Islam known more extreme in impeach the President. If the President has violated the social contract or betraying the country, the people can exercise his power through violence, war and even to murder though. While in constitutional law, if the president is no longer considered eligible as President, then drop by the President from office or deliberations through the legal process set out in the Constitution 1945